The Relationship Between Sitting Position and Chronic Back Pain in Tailors at Elraffip Fashion - Ikhsan Hidayatulloh, Ana; Mardiana Hidayat, Fitriani; Putri Rayesi, Indira (HealthCare Nursing Journal, 2025)
One of the most common reasons patients seek emergency care is back pain. Mechanical back pain occurs in 90% of cases due to occupational factors where this injury can cause damage or degeneration to the spine or the discs that form it and this results in chronic back pain. The aim of this research is to determine the relationship between sitting position and chronic pain in the back of Elraffip Busana Kawalu convection tailors, Tasikmalaya City. The type of research that will be used is quantitative with a cross-sectional approach. The samples taken in this research were all tailors at the Elraffip Busana Kawalu Convection in Tasikmalaya City using total sampling techniques. The statistical test used is chi-square. The results of statistical tests show that there is a relationship between sitting position and chronic pain in the back of Elraffip Busana Kawalu convection tailors, Tasikmalaya City with a value of p = 0.013 (p > 0.05). In conclusion, there is a relationship between sitting position and chronic back pain in tailors at the Elraffip Busana Kawalu Convection, Tasikmalaya City